Dual-responsive shape memory hydrogels with novel thermoplasticity based on a hydrophobically modified polyampholyte1. Issue 21 (7th June 2015) - Fan, Yujiao; Zhou, Wanfu; Yasin, Akram; Li, Huazhen; Yang, Haiyang
<x xml:space="preserve">Abstract</x> We report a dual responsive shape memory hydrogel with novel thermoplasticity that facilitates the change of the permanent shape.